World-ranking performance in judo athletes with visual impairment: An approach considering sport classes and weight categories - Kons, R. L.; Haegele, J. A.; Detanico, D. (British Journal of Visual Impairment, 2021)
The objective of this study was to analyze the ranking scores in Paralympic judo athletes in different visual impairment classifications (B1, B2, and B3) and describe the frequency of athletes of each classification allocated in the first five and last five positions in the ranking list. A total of 488 judo athletes with visual impairment (332 male and 156 female) took part in this study. Data were extracted from the Official Ranking List, documented and organized by the International Blind Sports Federation, and analyzed according to sport classes (B1, B2, and B3) and weight categories. One-way analysis of variance was used to compare the scores among different groups. The main results showed that B1 athletes presented lower total and best scores compared to B2 and B3 counterparts in both female (p = .020, p < .001, respectively) and male groups (p = .010, p = .005, respectively). In addition, when analyzing the ranking list position, there was a higher percentage of B1 athletes in the last five positions in female (60%) and male groups (60%) than B2 and B3 athletes. Investigations about classification and competitive system can assist coaches and sports organizations to identify the appropriateness of the ranking system scores adopted for athletes with visual impairment. Our findings showed some issues when considering competitive programming that includes all visual impairment classes in the same category.